2021
DOI: 10.1111/asap.12253
|View full text |Cite
|
Sign up to set email alerts
|

Metadehumanization erodes democratic norms during the 2020 presidential election

Abstract: The present research directly replicates past work suggesting that metadehumanization, the perception that another group dehumanizes your own group, erodes Americans' support for democratic norms. In the days surrounding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Using similar measures, other scholars found that the blatant dehumanization of Muslim and Mexican immigrants predicted support for hostile policies towards them (e.g., Muslim ban; solitary confinement of undocumented immigrants), controlling for affective prejudice [90]. Similarly, work finds that partisan blatant dehumanization predicts obstructionism and outgroup spite controlling for prejudice [62,63]. Examining implicit dehumanization, one group found that the implicit association between African Americans and apes predicted the condoning of violence directed by police officers at a Black suspect controlling for explicit racial prejudice [53].…”
Section: Box 4 Distinguishing Dehumanization From Dislikementioning
confidence: 97%
See 3 more Smart Citations
“…Using similar measures, other scholars found that the blatant dehumanization of Muslim and Mexican immigrants predicted support for hostile policies towards them (e.g., Muslim ban; solitary confinement of undocumented immigrants), controlling for affective prejudice [90]. Similarly, work finds that partisan blatant dehumanization predicts obstructionism and outgroup spite controlling for prejudice [62,63]. Examining implicit dehumanization, one group found that the implicit association between African Americans and apes predicted the condoning of violence directed by police officers at a Black suspect controlling for explicit racial prejudice [53].…”
Section: Box 4 Distinguishing Dehumanization From Dislikementioning
confidence: 97%
“…Individuals' meta-perceptions generally tend to be more negative than reality warrants (e.g., [106]). The same is true of dehumanization: American political partisans think members of the other party dehumanize them nearly three times more than is actually the case [62,63]. Fortunately, meta-dehumanization appears to be corrigible: informing non-Muslim Westerners that Muslims in the Middle East consider them fully human reduces their blatant dehumanization of Muslims [104,107], particularly among those who perceive Muslims to be most threatening at baseline [107].…”
Section: Theoretical Challenges To Dehumanization Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…These considerations inspired our attempt to reduce dehumanization in a context marked both by high levels of dehumanization and highly inaccurate meta-dehumanization. 1 Exaggerated Meta-Dehumanization Among American Partisans Substantial numbers of Democrats and Republicans explicitly, blatantly dehumanize one another (Cassese, 2021;Landry, Ihm, Kwit & Schooler, 2021;Moore-Berg et al, 2020). Perhaps because of its overt nature, partisans recognize that out-partisans explicitly, blatantly dehumanize them and even think they do so to a far greater extent than is actually the case.…”
Section: Reducing Dehumanization By Targeting Meta-dehumanizationmentioning
confidence: 99%